50th Anniversary of the death of Hugo Pesce Pescetto MD. (1969-2019) - Burstein Alva, Zuño (2019)
On July 26 of the present year 2019, 50 years of the unfortunate physical disappearance, at 69 years of life, of one of the most outstanding doctors of Peru, salubrious, leprologist, avant-garde and humanist intellectual, Prof. Dr. Hugo Pesce Pescetto (1900-1969). In the present article a reminder note is presented about his outstanding career and the posthumous tributes he received.